The Impact of Sustainability Disclosure Quality on the Analyst's Forecasts - Khaled , Dr. Bubaker K (Dirasat in Economics and Business, 2022)
This paper examines the imp-act of the quality of sustain-ability disclosure (QSD) on the accuracy of analyst’s earnings forecast. The study uses data fr-om 1900 firm-year observations drawn from Egypt stock exchan-ge covering 2009 to 2018. The results show evidence indi-cates that QSD mitigates information asymmetry by signalling QSD and improving the accuracy of analysts’ forecast. In addition, this study distinguishes between the quantity and the quality of sustainability disclosure and ex-amine their relationship with the accuracy of analyst forecast. The empirical results confirm that the QSD and its dimensions considered in the study framew-ork give more realistic discl-osure picture than quantity does. The results from the additional analysis also confirm the main result.